Application of high reliability theory in the water utility sector - Bradshaw, R. A. (Cranfield University, 2008)
In the literature, a need was identified to consider the provision of drinking water to be a ‘high reliability’ societal service. This thesis reports on an investigation into the technical and organisational reliability of a defined section in the water utility sector and a Regional Water Utility. Here, the organisational reliability in operations and incident management, and, secondly, the management of technical reliability of water supply systems arising from risk-based asset management were the emphasis of this project. In order to substantiate this investigation, three main research components were designed and conducted: firstly, a characterisation of the nature of incidents and their impact on customers; secondly, an investigation into organisational capabilities to manage incidents and its role in maintaining a resilient water supply system that minimises the impact of incidents on customers, and thirdly, an investigation into riskbased asset management strategies that provide and maintain the technical reliability of the water supply system. In the latter perspective, the opportunity to learn from previous incidents to enhance asset risk assessments was investigated. In this study, it was found that many HRO principles are readily observable in the water utilities that participated in this research. Following the characterisation of incidents, it is demonstrated that the observation of HRO principles during incident management has a positive effect on the overall reduction of incident impacts on customers. Beyond the immediate effect of HRO principles in incident management, it could be demonstrated that ‘learning from failure’ provides a mechanism to understand and manage future risks. The concept of incident meta-analysis is introduced that compares series of past incidents with documented perceived, future risks. The statistical analysis of incident time series facilitated the monitoring of incident trends, the validation of the risk model used in the Regional Water Utility and the verification of risk data, in particular for the risk components ‘probability, cause, effect and impact’.